(3cTa GdeQGO aj TQM JLQjO GdGYJbGOs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
... (3bhdg hjfMUQ Ydi ebOQ eVGa ehUha HUaI eNUhUI (B... (3HGdfbWI hGdhMOI Yf GdebGd ehLhO heeG aj (B... (3aEfg bjd HeG Ydi JbOjQ hLhO eeG aj (B...s
(3BNQgG (B:s
... (3Cf jfaYd hjaYd Ydi GdGfaYGd hGdaYd dCfgG bO jbGdGf ddMGUd HYO GfbWGY GdMQcI hdgeG GdebhdI deG cGf cGf JhLgG dG ZGjI efg hVY Ch cja Ch ZjQ Pdc (B... (3Jc GdebUO GdKGK aj BHGJ GdUGfYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B2/227s
(3GdPQjYI (B18 - 40 ( 668)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds